Anisotropic Plasmonic Nanostructure Induced Polarization Photoresponse for MoS2‐Based Photodetector. Issue 9 (8th March 2020) - Chen, Si; Cao, Rui; Chen, Xing; Wu, Qing; Zeng, Yonghong; Gao, Shan; Guo, Zhinan; Zhao, Jinlai; Zhang, Meng; Zhang, Han
Abstract: Techniques that give anisotropic properties to 2D materials with isotropic crystal structures will enable 2D material based photodetectors to possess polarization sensitivity in the detection of polarization, which will greatly improve the spatial resolution of photodetectors. Here, an MoS2 ‐based polarization photodetector induced by anisotropic plasmonic nanostructure is prepared. The integrating anisotropic plasmonic structures on a few‐layer MoS2 nanosheet can induce polarization photoresponse and enhance the responsivity of MoS2 device at the same time. The ratio of the maximum to minimum photocurrents reached 1.45 along two perpendicular polarizations. It proves that anisotropic nanostructure induced polarization sensitivity will pave a new way for the fabrication of polarization photodetectors. Abstract : The gold‐MoS2 hybrid polarization photodetector with anisotropic gold nanoellipse array is designed based on the finite different time domain simulation and fabricated by micromachining technique. This device achieves the polarization detection of the 660 nm laser, and the ratio of the maximum to minimum photocurrents reaches 1.45 along two perpendicular polarizations.